Unchanged but undecided: Reproductive intentions among Ghanaian women following COVID-19 lockdowns in two large metropolises in Ghana - Veena Bhagavathi; Deda Ogum; Kofi Agyabeng; Dorcas Coker-Appiah; Fidelia N. A. Ohemeng (PLoS ONE, 2025)
Evidence suggests that disaster situations such as the COVID-19 pandemic may affect reproductive intentions. These effects interact with an individual’s social context, including socioeconomic status, cultural norms, family size and structure, to shape reproductive intentions. In this paper, we review the COVID-19 lockdowns’ effects on reproductive intentions among Ghanaian women living in Accra and Kumasi. A correlational quantitative research design was adopted for the study while data was obtained through a survey of 532 women of reproductive age. Descriptive statistics, bivariate modeling using Chi-square and Fisher’s exact tests and multivariate modeling using Firth’s logistic regression model were conducted to understand determinants of changing intentions following the COVID-19 lockdowns. In all, 25 women (4.7%) reported changing their intentions. Those who come from Kumasi were more likely to change their intentions (p < 0.001) as were those who reside within their respective metropolis (p < 0.05). Those who had ever been married or cohabitated with a partner (p < 0.01), who have their childrearing decisions made with input from their partner or other family members (p < 0.05), and who were pregnant or expecting to become pregnant before the lockdowns were enforced (p < 0.001) were also more likely to change their minds. Residence in Kumasi (AOR = 4.21, 95%CI 1.41–12.62) and being pregnant or expecting to become pregnant just before lockdown (AOR = 4.29, 95%CI 1.28–14.32) were the strongest predictors for changing of intentions. Overall, reproductive intentions among those surveyed were largely characterized by ambivalence and inconsistency, with the largest groups of people labeling their state prior to COVID-19 lockdowns as “undecided” and their change in state after lockdown also as “undecided.” Future work should include more room for ambiguity when characterizing reproductive intentions among Ghanaian women. Incorporating room for ambiguity in characterizing reproductive intentions may improve accuracy in data collection in demographic health research and shift how success is measured in family planning policy. We hope that this shift will promote individualized and person-centered care in the realm of family planning.